The effects of high volume nano palm oil fuel ash on microstructure properties and hydration temperature of mortar - Lim, N.; Ismail, Mohamed; Lee, H.; Hussin, M.; Sam, A.; Samadi, M. (Elsevier BV, 2015)
© 2015 Elsevier Ltd. All rights reserved. The effect of high volume nano palm oil fuel ash in the mortar was investigated. This study covers basic properties like the morphology of the composite, the hydration temperature, strength activity index, thermal conductivity and microstructure properties with regards to the variations in the mix design process of mortar. The effects of fineness of the ash on the strength properties of mortar were also investigated. To get a better performance in terms of strength development, the ash used has gone through heat treatment and was ground up to less than 1 µm. The incorporation of more than 80% nano size palm oil fuel ash as cement replacement has produced a mortar havin g a compressive strength more than OPC mortar at a later age. The overall results have revealed that the inclusion of high volume nano palm oil fuel ash can produce a mortar mix with high strength, good quality and most importantly that is more sustainable.